Ecological Change, Agricultural Development and Food Production in Malawi: a Historiographical Review (The Strategic Review for Southern Africa, 2020)
Given its economic significance, agriculture has been at the centre of historical scholarship in Malawi. Yet despite the significant contribution this scholarship has made to the country’s development, there has been no effort to systematically reconstruct Malawi’s agricultural historiography. This article, therefore, takes stock of the progress that has been made by historians on research in the country’s agricultural history since the mid-1950s. The ultimate goal is to establish not only what might be regarded as the country’s agricultural historiography, but also the place of food production, which has become an important food security aspect of most Malawian peasants. After assessing the earlier works, the study observes that Malawi has an agricultural historiography which, prompted by the political and economic thoughts of the time, has conceptually evolved after the traditions of modernisation, underdevelopment and social history schools. It is argued here that, despite raising a strong case about the processes by which colonialism and capitalism disrupted peasant food economies, the historiography has made little effort to explore the patterns of peasant food production that emerged through this process, except for those studies that sought to understand the growth of famine and hunger. While resonating in many respects with the agricultural historiography of southern Africa, the Malawi case has gone beyond to include smallholder irrigation farming, which despite being globally recognised as a panacea for maintaining food production in the changing climate, has been under researched even in the dominating regional climate historiography.